Transitional Housing Facilities for Women Leaving the Sex Industry: Informed by Evidence or Ideology? - Dewey, Susan; Hankel, Jennifer; Brown, Kyria (Sexuality & Culture, 2017)
This article juxtaposes the results of descriptive and inferential statistical analysis, derived from 125 client case files at a Denver transitional housing facility for women leaving the sex industry, with the results of a content analysis that examined how all 34 similar U.S. facilities represent themselves, their clients, and their services on their websites. Content analysis results ascertained four primary findings with respect to transitional housing facilities for women leaving the sex industry, including their conflation of sex trading with sex trafficking, dominance by Christian faith-based organizations, race-neutral approach, and depiction of their clients as uneducated and socially isolated. Yet our statistical analysis revealed that significant differences exist between women's sex industry experiences in ways that are strongly determined by ethno-racial identity, age, marital status, and exposure to abuse throughout the life course. Juxtaposing the results of these analyses highlights some rather glaring disconnects between the ways that facility websites depict their clients and the meaningful differences between women seeking services at the Denver transitional housing facility. These findings raise significant concerns regarding approaches that ignore ethno-racial differences, collapse the sex industry's complexity, make assumptions about the women's educational or other needs, and neglect the importance of women's community and relational ties. Taken together, these troubling realities suggest a need for evidenced-based, rather than ideology-based, alternatives for women who wish to leave the sex industry.